Capture by Strong Knowledge as an Important Condition of Patriotic Education of Young People: Conception of Vasyl Sukhomlynskyi - Zavhorodnia, Tetiana (Pedagogical Discourse, 2016)
In the article the question of necessity of increase of efficiency of education is reflected at the young generation of active patriotically-civil position, realization of itself by part of the people. The existent problems of patriotic education of modern youths and girls are exposed in the context of problems of becoming of civil society in Ukraine. On the basis of the statistical information which got by the known scientists, conclusions are done about an insufficient level at considerable part of young people of both political knowledge in general and concept of essence categories «patriotism», that negatively influences on the process of their socialization, level of formed of active civil position. Therefore on the today’s stage of development of society the necessity of increase of efficiency grows civil-patriotic education of young people. To the problem of becoming of schoolboy as particles of the Ukrainian people with strong scalene knowledge the devoted researches of many scientists. Among them and prominent teacher of the ХХ century Vasyl Oleksandrovych Sukhomlynskyi. In the article an attempt is done on the basis of analysis of all labours of teacher, study of experience of activity of Pavlyskoi of school to ground pedagogical conception of Vasyl Sukhomlynskyi, that the necessary condition of patriotic education of young people is a capture by her by strong knowledge, that, on persuasion of teacher, are basis of activity of man for the good of Motherland. Named the basic ways of intensification of patriotic education of young people of V. Sukhomlynskyi: the permanent reading, forming for student’s young people of «spiritual» requirement in reading; bringing in of every student is to various creative labour that would require thorough scalene knowledge necessarily; conditioning is for the «independent reading of teacher», forming of his culture of reading. Terms, the observances of that, on persuasion of teacher, will assist the increase of efficiency of breeding for the students of patriotism in studies, are marked in the article. Key words: capture, patriotic education, pedagogical conception, active citizenship, values, Vasyl Oleksandrovych Sukhomlynskyi.